EFFECT OF DAMAGES ON THE STRESS-STRAIN STATE OF THE BUILDING UNDER STATIC AND DYNAMIC LOADS - Кичаева, О. В.; Михалёв, С. Д. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article analyzes the results of a numerical investigation of the stress-strain state of the building damaged by the static and dynamic loads. Keywords:stress-strain state, damage, numerical researches.